Ustavno- in primerjalno pravni vidiki kolektivnega upravljanja pravic na avdiovizualnih delih - Drobež, Eneja (Dignitas (Ljubljana), 2025)
the latest amendment to the Copyright and Related Rights Act from 2022 has significantly reshaped the relation-ships between key stakeholders in the creation of audiovis-ual works, i.e., co-authors, performers, and film producers. Slovenia has followed recent trends in comparative law,which ensure fair participation of creators in revenues from the secondary exploitation of audiovisual works through ir-revocable and non-transferable remuneration rights. this strengthens the position of collective organisations in theeuropean Union, as national laws for such rights usually stipulate that they must be managed collectively. on the other hand, due to the constitutional right to legal security, it is necessary to prevent the new legal provisions from interfering with existing contractual relationships between creators and film producers. In this article, we will examine the nature of the new rights and compare them with simi-lar regulations in comparative law. We will examine which of these rights could pose a challenge in terms of the pro-hibition of retroactive effect of rights and how legislators should approach this issue.
Keywords: audiovisual works; avdiovizualna dela; avtorsko pogodbeno pravo; copyright contract law; Človekove pravice; development of copyright legislation; poplačilne pravice; pravice do nadomestil; prepoved povratne veljave predpisov; prohibition of retroactive effect of regu-lations; razvoj avtorskopravne zakonodaje; remuneration rights